Prevalence of thyroid dysfunction in type 2 diabetics - Prakash, Vivek; Marker, Sebastian; Rao, Kaavya; Nawal, C. L.; Chejara, R. S. (International Journal of Research in Medical Sciences, 2020)
Background: Type 2 Diabetes Mellitus has emerged as a common endocrine disorder in india. Thyroid dysfunction may complicate glycaemic control of diabetic patients. For better management of diabetes, it is necessary to detect and treat thyroid dysfunction in these patients. Methods: This was an observational study conducted at SMS Hospital Jaipur, Rajasthan, India, between March 2016 to November 2017. Total 100 patients were included out of which 50 were Diabetic patients and 50 were age and sex matched nondiabetic controls reported in outpatient department of SMS Hospital, Jaipur. Patients of type 1 Diabetes, previously known case of thyroid disorder, patients having endocrine disorder or autoimmune disorder other than Diabetes, critically ill patients and pregnant females were excluded from study. Serum Fasting Blood Sugar, Free T3, Free T4, TSH were measured in all study subjects and results were analysed statistically to find out if there is any difference in prevalence of thyroid dysfunction in Diabetic patients and non-diabetic controls. Results: Thyroid dysfunction was present in 16 (32%) of 50 type 2 diabetics and 3 (6%) of 50 nondiabetic controls. The prevalence of thyroid dysfunction in type 2 diabetic females and males was 43.3% and 15% respectively. Mean fasting blood sugar was higher in diabetic patients having thyroid dysfunction (209.12 mg/dl) as compared to euthyroid diabetic subjects (173.58 mg/dl). Twelve (75%), out of 16 study subjects with thyroid dysfunction have secondary hypothyroidism. Three (18.75%) of them have mild (sub-clinical) hypothyroidism. One person (6.25%) has subclinical hyperthyroidism. Conclusions: Prevalence of thyroid dysfunction is higher in type 2 diabetic patients as compared to nondiabetic. Better glycaemic control is observed in euthyroid diabetic patients as compared to diabetic patients having thyroid dysfunction.